Design, Synthesis and Acetylcholinesterase and Butylcholinesterase Inhibition Activity of Novel 1-(Alkyl)-3-(2-oxo-2H-chromenyloxy Acetamido) methylpyridinium Salts - fard, Mehri A.; Manafi, Mohammadreza; Motevalian, Manijeh; Homami, Seyed Saied (Letters in Organic Chemistry, 2021)
In this paper, a novel series of 1-(alkyl)-3-(2-oxo-2H-chromenyloxy acetamido) methylpyridinium salts were synthesized in a simple and efficient way. The method showed to be facile and the compounds were obtained in high isolated yields. All the synthesized compounds were characterized by 1H NMR, 13C NMR, FT-IR, Mass and elemental analysis. AChE and BuChE inhibition activity of the synthesized compounds were evaluated and the results showed that all the compounds were active in the inhibition of the mentioned enzymes. All the compounds were active in the inhibition of the two studied enzymes. Among all the compounds, the compound 6a (1.85 μM) and 6i (0.106 μM) showed the highest inhibition activity against AChE and BuChE, respectively. The kinetic study was performed to get more insight into the mechanism of action of the synthesized compounds. Docking studies were also performed to obtain the interactions between the synthesized compounds and the enzymes.
Keywords: BuChe inhibition